Harmonizing Standards: Implementation and Learning Challenges in a Dual-Curriculum System - Ahmad Sahrul Hamdani; Fariyatul Aini; Siti Nurafida (UIN Siber Syekh Nurjati Cirebon, 2025)
This study aims to describe the model of Cambridge Curriculum integration at MTsN 6 Malangand to identify the challenges encountered during its implementation. The research employed adescriptive qualitative approach with data collected through interviews and classroomobservations involving the Vice Principal for Curriculum Affairs and the International ClassProgram (ICP) teachers. The findings reveal that MTsN 6 Malang adopts a selective-adaptiveintegration model by combining three core subjects Mathematics, Science, and English alignedwith the national curriculum. The teaching process employs a bilingual approach, using Englishas the primary medium of instruction and incorporating active learning strategies to promotecritical thinking and communicative skills. The assessment system integrates national standardswith the Cambridge Checkpoint to maintain academic consistency. Major challenges includestudents’ readiness to comprehend foreign-language materials. The institution addresses theseissues through English matriculation programs. The study provides empirical insights into howIslamic schools integrate international curricula while upholding religious and national values.